THE RELATIONSHIP AMONG PARENT’S ATTENTION AND UTILIZATION OF LEARNING RESOURCES WITH LEARNING ACHIEVEMENT OF MATHEMATICS STUDENTS - Eva Wempianada; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
Results of low mathematics associated with many factors. Parent’s attention and utilization of learning resources are two factors that allegedly associated with the learning achievement of mathematics students. This research has to determine whether or not a positive and significant relationship between parent’s attention and utilization of learning resources with students mathematics learning outcomes in class X of even semester in Muhammadiyah Senior High School 5 Yogyakarta (SMA Muhammadiyah 5 Yogyakarta) academic year 2016/2017. The population in this research was all students of class X in even semester in the academic year 2016/2017 with the total number of 190 students in 6 classes. Function random sampling technique to class to take a sample class, to obtain class D as a class of research and class X C as a trial class. Data collection techniques are done with the documentation method, questionnaire method, and the test method. The research instruments used are field records, questionnaires, and test questions. The instruments test used test of validity, reliability testing, and different power. Analysis of instrument trials using the normality test, independent test, and linearity test. Data analysis using linear regression analysis and correlation analysis. The results showed a positive and significant relationship between parents' attention and the utilization of learning resources with mathematics learning outcomes with a learn regression equation Ŷ = 24,624 + 0,556 X1 + 0,402 X2 and multiple correlation coefficient ( ) of 0,834. As well as obtained 28,618 and 3,39, so . Relative contribution of (X1) 64,162% and (X2) 35,838% with coefficient of determination was 0,696 and effective contribution (X1) 44,657% and (X2) 24,943%.